Discrimination ability of ASDAS estimating disease activity status in patients with ankylosing spondylitis - Nas, Kemal; Yildirim, Kadir; Cevik, Remzi; Karatay, Saliha; Erdal, Akin; Baysal, Ozlem; Ozgocmen, Salih (Wiley-Blackwell, 2010)
Objectives: To investigate discrimination ability of the Assessment of Spondyloarthritis International Society (ASAS) endorsed disease activity score (ASDAS) versions evaluating low and high disease activity in an unselected group of patients with ankylosing spondylitis (AS). Methods: Patients consecutively included into the joint database of five university hospitals were analyzed for low or high disease activity according to different criteria. Standardized mean differences (SMD) for two ASDAS versions were evaluated. Results: The ASDAS versions (back pain, morning stiffness, patient global pain, pain/swelling of peripheral joints, plus either erythrocyte sedimentation rate or C-reactive protein) discriminated high and low disease activity in subgroups according to Bath Ankylosing Spondylitis Disease Activity Score (BASDAI) and ASAS remission/partial remission criteria. ASDAS versions were also not influenced by peripheral arthritis and correlated well with other outcome measurements and acute-phase reactants. The ASDAS versions performed better than patient-reported measures or acute-phase reactants discriminating high and low disease activity status. Conclusion: Both ASDAS versions, consisting of both patient-reported data and acute-phase reactants, performed well in discriminating low and high disease activity. Further longitudinal data may better estimate the usefulness of ASDAS to assess disease activity subgroups and treatment response.
Keywords: ankylosing spondylitis; ASDAS; disease activity